Road to comprehensive estimation of antimicrobial resistance (AMR) disease burden in Japan - Tsuzuki, Shinya (Glob Health Med, 2020)
Antimicrobial resistance (AMR) is currently a global health threat. Many countries have issued their own national action plans following the publication of the Global Action Plan on AMR by the World Health Organization. The government of Japan established its own National Action Plan on AMR in 2016; however, Japan's AMR countermeasures are still in the developmental stage. Recently, the AMR Clinical Reference Center (AMR CRC) in Japan estimated the disease burden of AMR in the form of number of deaths attributed to blood-stream infections caused by antimicrobial-resistant organisms. However, a more extensive and precise assessment is needed to understand the disease burden of AMR more clearly and enable us to compare these indicators with those published by other countries. Cassini and colleagues from the World Health Organization estimated the disease burden of AMR in the European Union as disability-adjusted life years (DALYs) in 2018. Their study could be considered an important milestone in terms of its thoroughness. If we hope to estimate the disease burden of AMR in a more precise manner, age-stratified patient data is needed in conjunction with a surveillance report. At present, AMR CRC is attempting to establish such data for examination at the national level - a challenging but worthwhile task.